Manganese availability and transformations in soil profiles under different wheat based cropping systems in north-western India - MITTAL, SHREYANSH; PAL SAINI, SAT; SINGH, PRITPAL (The Indian Journal of Agricultural Sciences, 2022)
Long-term (>10 years) changes in depth-wise distribution of DTPA-Mn and Mn fractions of variable solubilityin soils under three different cropping systems, viz. rice-wheat (RWCS), maize-wheat (MWCS) and cotton-wheat(CWCS) in Ludhiana, Ropar and Mansa districts of Punjab, north-western India were studied during 2005–18. Thesurface (0–15 cm) layer of soils under RWCS had significantly lower (by ~31.8%) DTPA-Mn concentration, comparedto MWCS. The surface soils under CWCS had ~18.4% higher DTPA-Mn than the soils under RWCS. The DTPA-Mnincreased significantly with increased depth of soils under RWCS, in contrast to a significant decrease in MWCS andCWCS. A sequential extraction of Mn in different fractions of variable solubility revealed that the surface layer ofsoils under RWCS had significantly lower concentration, while the lower layers had higher concentration. The Res-Mn fraction comprised the largest proportion (67–70%) of total-Mn in soils under different cropping systems. The(WSEX+SpAD)-Mn fraction was the smallest Mn fraction of high solubility, comprising ~2–3% of total-Mn in soilsunder different cropping systems. The relative distribution of different fractions was OM-Mn≤WSEX-Mn≤SpADMn